New Towns Development: A Wave of the Future Planning Practices in Nepal - Dahal, Kedar; Timalsina, Krishna Prasad (Tribhuvan University Journal, 2017)
Increasing urbanization has been a major challenge to tackle issues relating to population growth, housing, infrastructure development and urban management in Nepal. Initiatives have been taking by the stakeholders of urban sectors in different course of action plans. New town development, smart city development, preparation and implementation of various strategic plans and action plans are some of the initiatives undertaken by the Ministry of Urban Development, Government of Nepal. At present, the Ministry of Urban Development is preparing intervening plans and programmes to 40 towns for planned urban development in Nepal. Some of these towns are already in pace of development and some others are in infancy stages. Balance urban development strategy so far is a strategy of government of Nepal however theory of political economy of development is inherently coming in selection of the towns, and basically in implementing the plans. Therefore, most of the prepared action plans are in question of effective implementation. Among the prioritized new towns of Nepal, some of these towns particularly smart cities are in very infancy stages of infrastructure development in which ‘smartness’ itself falls into huge dilemma. Therefore, more challenges are added in implementing the smart cities into action plan. However, new towns of Hilly and Tarai-Madhesh area will definitely provide the opportunities to cater population and create more opportunities. In this context, this study focus on the new town development and their spatial distribution in Nepal through the collection of primary information and review of previous literature.